EVALUATION OF MOTHER AND CHILD HEALTH (MCH) HANDBOOK: A SYSTEMATIC REVIEW - Wike Pratiastuti; Ahmad Syafiq (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: Maternal and Child Health (MCH) handbook is a home-based health record for both mother and child. The handbook can be used to monitor the health of women and her child, to give record in the utilization of health services, promote maternal health education, and provide information when either mother or child is referred. Several countries adopted the MCH handbook as a tool to promote better health knowledge and health service seeking behavior among women, and numerous countries have succeeded in applying it. Therefore a strategy is needed to improve the effectiveness and efficiency of the MCH handbook with strong evidence. This study aims to evaluate the effectiveness and efficiency the implementation of the recording, information and education usefulness of the MCH handbook. Methods: Using systematic review method, the literature review using PICOS was employed 3 articles with PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analyses) approach by taking sources from online database: Proquest, Jstor, Pubmed, EBSCO, Science Direct and Scopus. Results: Previous studies from three (3) countries stated that the contents of the MCH handbook were complete which included the ANC (antenatal care) record, delivery, PNC (post-natal care), child development, notification of birth, an educational message to raise the demand and awareness of healthy behavior of women in pregnancy and motherhood and improve their essential service utilization. For use of the MCH handbook in 3 countries it is known that almost are used to record all health and treatments consultations during pregnancy, delivery, after delivery and during infant care, including immunization and growth monitoring (birth weight is accurate data to monitor stunting in children under 5 years), maternal and neonatal death surveillance and response records. In Burundi, it is also used in birth registration procedures. Conclusions: The MCH handbook is an effective health education tool for women with less education, a reliable source of information for primiparous women, delivery, and childcare; and an effective aid for health communication between women and health providers, and their husbands.